Ответы и объяснения

2014-02-15T18:22:45+04:00
Возведем все в 6 степень и у нас получится
\sqrt[6]{(2x^2-2)^6} = \sqrt[6]{(4x-1)^6} \\ 2x^2-2=4x-1 \\ 2x^2 -4x-1=0 \\ D=16+4*2*1=24 \\ \sqrt{D}= \sqrt{24}= \sqrt{4*6}=2 \sqrt{6} \\ x1= \frac{4-2 \sqrt{6} }{4}= \frac{2(2- \sqrt{6}) }{4}= \frac{2- \sqrt{6} }{2}= \frac{2}{2}- \frac{ \sqrt{6} }{2}=1- \frac{ \sqrt{6} }{2}    \\ x2= \frac{4+2 \sqrt{6} }{4}= \frac{2(2+ \sqrt{6}) }{4}= \frac{2+ \sqrt{6} }{2}=\frac{2}{2}+ \frac{ \sqrt{6} }{2}=1+ \frac{ \sqrt{6} }{2}
Ответ x=1+ \frac{ \sqrt{6} }{2}
Лучший Ответ!
  • fanat2
  • главный мозг
2014-02-15T18:43:35+04:00